Prediksi Kebangkrutan Perusahaan Yang Berorientasi Ekspor Pada Masa Krisis - Fongnawati Budhijono; Ria Indahsari (Universitas Multimedia Nusantara, 2009)
The impact of the global crisis has attack Indonesia, not only in the financial sector but also in other sectors. In the manufacturing sector, it is seen from the decline in industrial performance of export-oriented manufacturing because of reduced demand. Bankruptcy potential a business entity at a time of crisis was questionable. This study was conducted to predict bankruptcy in crisis conditions. This study aims to obtain empirical evidence of the bankruptcy potential of industry 'textile mill products' and 'apparel and other textile products' exportoriented listed in Indonesia Stock Exchange in crisis conditions. Data from 14 publicly listed firms In Indonesia in the year 2008 were used. The research result shows that: (1) By using the analysis of financial ratios known that there were as many as three issuers are not bankrupt in conditions of crisis, eleven issuers are bankrupt in conditions of crisis. (2) By using the Altman Z Score is known that there are one issuer that are not included in the category of bankrupt, two issuers included in the category of grey area and eleven issuers located in the category of bankrupt.(3) The result of bankruptcy prediction based on financial ratios has similarity in conclusion as the result based on Altman Z Score. Key words : bankruptcy, financial ratio, Altman Z-score